Bullous Pemphigoid Treated with Corticosteroid: A Case Report - Dwi M. Trisnowati; Hyacintha P. Budi; Shienty Gaspersz; Meilany Durry (Universitas Sam Ratulangi, 2022)
Abstract: Bullous pemphigoid (BP) is an autoimmune disease clinically characterized by pruritic, large, tense subepidermal bullae over normal skin, erythematous or urticarial plaques. The pathogenesis related to the immune system towards BP antigen 180 and 230. Mild lesions may be treated with topical corticosteroid but the more extensive lesions are treated with oral corticosteroids. We reported a case of 58-year-old man came with clear fluid-filled blisters on the body since a week ago. Dermatological examination revealed multiple vesicle-bullae, filled with clear fluid, tense walls. Nikolsky sign and Asboe-Hansen sign were negative. Histopathological examination supported the diagnosis of BP. Diagnosis was established based on anamnesis, and physical and histopathological examinations. The patient was treated with systemic corticosteroid due to the consideration of the extensive lesions. Methylprednisolon was given intravenously at a dose of 43.75 mg per day which was then replaced orally for tapering off. The dose reduction of 4 mg per week was carried out according to the clinical improvement. In conclusion, this case improved after being treated with systemic corticosteroid for approximately 2-3 months.Keywords: bullous pemphigoid; corticosteroidÂ Abstrak: Pemfigoid bulosa (PB) merupakan penyakit bula autoimun ditandai dengan pruritus dan bula subepidermal besar berdinding tegang di atas kulit yang normal, eritematosa atau plak urtikaria. Patogenesisnya berhubungan dengan sistem kekebalan tubuh yaitu respons imun terhadap antigen BP 180 dan 230. Penatalaksanaan untuk lesi ringan diberikan kortikosteroid topikal, sedangkan untuk lesi luas dengan kortikosteroid sistemik. Kami melaporkan seorang laki-laki berusia 58 tahun dengan keluhan lepuh-lepuh berisi cairan jernih pada hampir seluruh tubuh sejak satu minggu lalu. Pada pemeriksaan fisik ditemukan vesikel-bula, multipel, berisi cairan jernih, dinding tegang. Pemeriksaan tanda Nikolsky dan Asboe-Hansen negatif. Pemeriksaan histopatologik mendukung diagnosis PB. Tatalaksana yang diberikan berupa kortikosteroid sistemik karena pertimbangan lesinya yang luas. Metilprednisolon diberikan secara intravena dengan dosis 43,75 mg per hari yang kemudian diganti pemberian per oral saat tapering off. Penurunan dosis 4 mg metilprednisolon per minggu dilakukan sesuai dengan perbaikan kondisi klinis. Simpulan kasus ini ialah pemfigoid bulosa yang mengalami perbaikan setelah diterapi dengan kortikosteroid sistemik selama kurang lebih 2-3 bulan.Kata kunci: pemfigoid bulosa; kortikosteroid